2020
DOI: 10.18502/ijaai.v19i3.3453
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Effects of Krocina™, a Herbal Medicine Made of Crocin, on Osteoarthritis Patients: A Successful Clinical Trial in Iran

Abstract: Osteoarthritis (OA) is the major cause of joint pain and disability. This research was planned to examine the effects of Krocina™, aherbal medicine made of crocin, an ingredient of saffron, in patients with OA. Forty patients suffering from OA were enrolled in our study and randomly divided into two groups, receiving Krocina™ and placebo, and the clinical trial continued for four months.Peripheral blood was taken from all patients and the percentage ofvarious subsets of T cells in addition to the levels of for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…Previous studies that have examined the effects of crocin or saffron consumption on inflammatory markers have yielded conflicting results. In agreement with our findings, some studies indicated that crocin or saffron had beneficial effects on TNF‐ɑ (Ghiasian et al, 2019; Mobasseri et al, 2020), NF‐κB (Abedimanesh et al, 2020), and hs‐CRP (Poursamimi et al, 2020). In contrast, other studies reported that the administration of saffron did not reduce inflammatory markers (Azimi et al, 2016; Ebrahimi et al, 2019; Hamidi et al, 2020; Kermani et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies that have examined the effects of crocin or saffron consumption on inflammatory markers have yielded conflicting results. In agreement with our findings, some studies indicated that crocin or saffron had beneficial effects on TNF‐ɑ (Ghiasian et al, 2019; Mobasseri et al, 2020), NF‐κB (Abedimanesh et al, 2020), and hs‐CRP (Poursamimi et al, 2020). In contrast, other studies reported that the administration of saffron did not reduce inflammatory markers (Azimi et al, 2016; Ebrahimi et al, 2019; Hamidi et al, 2020; Kermani et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Out of 139 studies screened in total, five RCTs and seven publications (two studies with duplicate publications) [27][28][29][30][31][32][33] fulfilled the protocol's criteria and were included in the systematic review. Figure 2 details the PRISMA 2020 flow diagram of the study selection process [19].…”
Section: Search Resultsmentioning
confidence: 99%
“…Details of the RCTs fulfilling the study's criteria, evaluating saffron interventions in patients with rheumatoid arthritis (RA), osteoarthritis (OA), or fibromyalgia (FM), the respective trials are detailed in Figure 3. The effect of saffron supplementation was evaluated in two trials using participants with RA [27,31,33], an additional two RCTs with patients with a knee OA diagnosis [28,29,32] and finally, on one RCT performed in patients with FM [30] (Figure 3). In RA, two different diagnostic criteria were employed, including the American College of Rheumatology/European league against Rheumatism (ACR/EU-LAR) 2010 [34] and the revised ACR 2017 [35].…”
Section: Rd Diagnosesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they found reduced expression of p-JNP, p-ERK, and p-p38, which are involved in the MAPK pathway, reducing airway inflammation (Xiong et al, 2015). Another study found that osteoarthritis patients given a daily treatment of 15 mg crocin for four months had a reduction of pro-inflammatory Th17 cells and an increase in regulator T cells as compared to the starting point (Poursamimi et al, 2020). These studies highlight various immunological effects of saffron and its compounds.…”
Section: Immune-enhancing Propertiesmentioning
confidence: 90%